Key Role of Respiratory Quotient to Reduce the Occurrence of Hypoxemia During Extracorporeal Gas Exchange: A Theoretical Analysis*. Issue 12 (December 2020) - Cipriani, Elisa; Langer, Thomas; Bottino, Nicola; Brusatori, Serena; Carlesso, Eleonora; Colombo, Sebastiano Maria; Zanella, Alberto; Pesenti, Antonio; Grasselli, Giacomo
Abstract : Objectives: Extracorporeal respiratory support, including low blood flow systems providing mainly extracorporeal CO2 removal, are increasingly applied in clinical practice. Gas exchange physiology during extracorporeal respiratory support is complex and differs between full extracorporeal membrane oxygenation and extracorporeal CO2 removal. Aim of the present article is to review pathophysiological aspects which are relevant for the understanding of hypoxemia development during extracorporeal CO2 removal. We will describe the mathematical and physiologic background underlying changes in respiratory quotient and alveolar oxygen tension during venovenous extracorporeal gas exchange and highlight the clinical implications. Design: Theoretical analysis of venovenous extracorporeal gas exchange. Setting: Italian university research hospital. Patients: None. Interventions: None. Measurements and Main Results: While the effect of extracorporeal CO2 removal on the respiratory quotient of the native lung has long been known, the role of extracorporeal oxygenation in dictating changes in the respiratory quotient has been less addressed. Indeed, both extracorporeal CO2 removal and extracorporeal oxygen delivery affect the respiratory quotient of the native lung and thus influence the alveolar PO2 . Indeed, for the same amount of extracorporeal CO2 extraction, it is possible to reduce the FIO2, reduce the risk of absorption atelectasis, and maintain the same alveolar PO2, by increasing the extracorporeal oxygen delivery. Conclusions: Worsening of hypoxemia is frequent during low-flow extracorporeal CO2 removal combined with ultraprotective mechanical ventilation. In this context, increasing extracorporeal oxygen delivery, increases the respiratory quotient of the native lung and could reduce both the occurrence of alveolar hypoxia and absorption atelectasis, thus optimizing the residual lung function. Abstract : Supplemental Digital Content is available in the text.